Impact of preserved collateral veins on small‐for‐size grafts in living donor liver transplantation. Issue 4 (4th December 2017) - Kim, Seong Hoon; Lee, Eung Chang; Park, Sang Jae
Abstract : Aim: Graft size is a critical issue in living donor liver transplantation (LDLT). We hypothesized that too much portal flow could possibly be diverted into pre‐existing collateral veins, alleviating small‐for‐size syndrome (SFSS) in LDLT. This study evaluated the impact of the preserved collateral veins in the outcomes of LDLT using a small‐for‐size graft. Methods: For patient safety, a graft‐to‐recipient weight ratio (GRWR) <0.8% was strictly confined to patients with collateral veins (group A), and the patient group was compared in a 1:3 ratio to a matched group of patients with GRWR ≥0.8% (group B) using propensity score analysis. Results: Forty and 120 patients were included in group A and B, respectively. No significant differences in baseline patient characteristics were observed between the two groups except for graft weight and GRWR. The lowest GRWR was 0.4%. The graft portal inflow showed no significant differences for 7 days after graft implantation, ranging from 1668 to 5100 mL/min. Small‐for‐size syndrome occurred in no patients (0.0%) in group A and in 10 (8.3%) in group B ( P  = 0.067). Overall survival rates at 1, 3, and 5 years were not different between the two groups (85.0%, 82.5%, and 82.5% vs. 92.5%, 86.7%, and 85.0%, respectively; P  = 0.670). Conclusion: Pre‐existing collateral veins saved during surgery may have a reserve buffer for excessive portal flow to obviate SFSS in LDLT.